Management of hypothyroidism with combination thyroxine (T4) and triiodothyronine (T3) hormone replacement in clinical practice: a review of suggested guidance - Colin Dayan; Vijay Panicker (Thyroid Research, 2018)
Abstract Background Whilst trials of combination levothyroxine/liothyronine therapy versus levothyroxine monotherapy for thyroid hormone replacement have not shown any superiority, there remains a small subset of patients who do not feel well on monotherapy. Whilst current guidelines do not suggest routine use of combination therapy they do acknowledge a trial in such patients may be appropriate. It appears that use of combination therapy and dessicated thyroid extract is not uncommon but often being used by non-specialists and not adequately monitored. This review aims to provide practical advice on selecting patients, determining dose and monitoring of such a trial. Main body It is important to select the correct patient for a trial so as to not delay diagnosis or potentially worsen an undiagnosed condition. An appropriate starting dose may be calculated but accuracy is limited by available formulations and cost. Monitoring of thyroid function, benefits and adverse effects are vital in the trial setting given lack of evidence of safe long term use. Also important is that patients understand set up of the trial, potential risks involved and give consent. Conclusion Whilst evidence is lacking on whether a small group of patients may benefit from combination therapy a trial may be indicated in those who remain symptomatic despite adequate levothyroxine monotherapy. This should be undertaken by clinicians experienced in the field with appropriate monitoring for adverse outcomes in both short and long term.